Exterior view of the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
The Vyankatesh Balaji Temple has retained many of its original architectural features, including the Mangalore tiled roof, thanks to the effort of conservation architect Sudhir Joshi. The interior receives natural light through high windows on three sides. The windows have wooden balustrades which are indicative of the floor being used as a working space.